The Demographic Characteristics And Its Role In The Development of The Coastal Territory of Syria (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The coastal territory of Syria, in terms of its demographic characteristics, is remarkably rich of human resources where manpower records 65,1% of the total population. These statistics pose a big challenge regarding high levels of unemployment in the region, according to the results of 2004 Census. Such a magnitude of manpower and workforce, is an inevitable as well as an objective consequence of the previous phase of population growth in the region, which has seen a surge in fertility rates and population growth, leading into imbalance between supply and demand equation in the labour market, and the biggest challenge in the context of the development process itself as much as for future planning. Population and development have a dialectical relationship of bilateral paradox through which population variables constitute the cause and consequence of the development process conditions.